Navigating the Vaginal Milieu During Perimenopause: A Narrative Review of Physiological Changes and Clinical Implications - Megha Tiwari; Neema Acharya; Manjusha Mahakarkar (Journal of Pharmacy and Bioallied Sciences)
Perimenopause represents a transitional phase in a woman’s life, marked by significant hormonal and physiological changes that profoundly impact the vaginal milieu. These changes can lead to a variety of symptoms, collectively known as genitourinary syndrome of menopause, affecting a woman’s sexual health, quality of life, and overall well-being. This narrative review aims to explore the underlying physiological alterations in the vaginal environment during perimenopause, their clinical implications, and current therapeutic approaches. By highlighting the challenges and emerging strategies in managing these changes, this review provides insights into personalized treatment options for improving women’s health during this crucial period.